Inflammation-Related DNA Damage and Cancer Stem Cell Markers in Nasopharyngeal Carcinoma - Shumin Wang; Ning Ma; Weilin Zhao; Kaoru Midorikawa; Shosuke Kawanishi; Yusuke Hiraku; Shinji Oikawa; Zhe Zhang; Guangwu Huang; Mariko Murata (Hindawi Limited, 2016)
Nitrative and oxidative DNA damage plays an important role in inflammation-related carcinogenesis. To investigate the involvement of stem cells in Epstein-Barr virus infection-related nasopharyngeal carcinoma (NPC), we used double immunofluorescence staining to examine several cancer stem/progenitor cell markers (CD44v6, CD24, and ALDH1A1) in NPC tissues and NPC cell lines. We also measured 8-nitroguanine formation as an indicator of inflammation-related DNA lesions. The staining intensity of 8-nitroguanine was significantly higher in cancer cells and inflammatory cells in the stroma of NPC tissues than in chronic nasopharyngitis tissues. Expression levels of CD44v6 and ALDH1A1 were significantly increased in cancer cells of primary NPC specimens in comparison to chronic nasopharyngitis tissues. Similarly, more intense staining of CD44v6 and ALDH1A1 was detected in an NPC cell line than in an immortalized nasopharyngeal epithelial cell line. In the case of CD24 staining, there was no significant difference between NPC and chronic nasopharyngitis tissues. 8-Nitroguanine was detected in both CD44v6- and ALDH1A1-positive stem cells in NPC tissues. In conclusion, CD44v6 and ALDH1A1 are candidate stem cell markers for NPC, and the increased formation of DNA lesions by inflammation may result in the mutation of stem cells, leading to tumor development in NPC.